PERANCANGAN PROGRAM APLIKASI PENGIRIMAN BARANG BERBASIS WEB PADA PERUSAHAAN PT NEXT COURIER - Abijan, Abijan; Rusdi, Zyad (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Supply Chain Management is the management of the flow of goods. It includes the movement and storage of raw materials, work-in process inventory, and finished goods from point of origin to point of consumption. Interconecred or interlinked networks, channels and node businesses are involved in the provision of products and service required by end customers in a supply chain. Supply chain management has been defined as the “design, Planning, execution, control, and monitoring of supply chain activities with the objective of creating net value, building a competitive infrastructure, leveraging worldwide logistics, synchronizing supply with deman and measuring performance globally Keywords Supply chain, business , product and services